Trinexapac-ethyl application time in the crop corn agronomic performance grown under different plant arrangements - Oliveira, Mariana Alves de; Zucareli, Claudemir; Barbosa, André Prechlak; Spolaor, Leandro Teodoski; Fantin, Lucas Henrique; Pricinotto, Luiz Henrique; Neves, Carmen Silvia Vieira Janeiro (Semina: Ciências Agrárias, 2022)
Reduced row spacing promotes more uniform spatial distribution of plants in the field. However, the adoption of reduced row spacing only is possible with smaller plants, which may be obtained with the use of plant growth regulator. This study aimed to evaluate the agronomic performance of the first corn crop with Trinexapac-ethyl applied at the different plant development stages and grown under different row spacing, with the same plant population. The experiments were arranged in a split-plot randomized block design with four replications, with row spacing for the plots (0.45 and 0.90 m) and Trinexapac-ethyl (TE) application time to subplots (control without application, at the V3, V6, V9 and V12 phenological stages). The Trinexapac-ethyl application time interacted with row spacings changing the growth and yield performance of the corn crop. For 0.45 m spacing Trinexapac-ethyl application at V12 and for 0.90 m spacing application at V9 and V12 reduced plant height and ear height. Trinexapac-ethyl application at V9 for both row spacings changed the plant architecture without changing the ear length and grain yield.